Factors associated with the patient’s decision to avoid healthcare during the COVID-19 pandemic - Soares, Patrícia (2022)
Funding Information: Funding: The present publication was funded support through CHRC (UIDP/04923/2020). Publisher Copyright: © 2021 by the authors. Licensee MDPI, Basel, Switzerland.